Metabolism and urinary excretion of 5-amino salicylic acid in healthy volunteers when given intravenously or released for absorption at different sites in the gastrointestinal tract. Issue 2 (February 1987) - Myers, B; Evans, D N; Rhodes, J; Evans, B K; Hughes, B R; Lee, M G; Richens, A; Richards, D
Abstract : In six healthy subjects serum concentrations of 5 amino salicylic acid (5ASA) and acetyl 5ASA were measured for up to 24 hours, and urinary excretion over 48 hours. After an intravenous injection of 3.26 mmol 5ASA serum concentrations fell rapidly with a distribution half-life of 17 +/- 2 min and an elimination half-life of 42 +/- 5 min. After 45 minutes acetyl 5ASA became the dominant compound and after seven hours serum concentrations of both components were almost unrecordable. Orally ingested 5ASA in three preparations to ensure its release in the stomach, small intestine and ileocaecal region respectively gave lower serum concentrations and urinary excretion than those obtained after an intravenous infusion. Bioavailabilities which ranged from 19% for ileocaecal release to 75% for release in the upper gastrointestinal tract, were calculated from areas under the serum concentration curves. Urinary excretion of 5ASA and its acetyl metabolite over 48 hours was 78%, 52%, 55%, and 21% respectively of the dose given intravenously and orally for gastric, small intestinal and ileocaecal release.